Effect of cardiorespiratory and strength exercises on disease activity in patients with inflammatory rheumatic diseases: a systematic review and meta-analysis. Issue 14 (28th April 2017) - Sveaas, Silje Halvorsen; Smedslund, Geir; Hagen, Kåre Birger; Dagfinrud, Hanne
Abstract : Objective: To investigate the effects of cardiorespiratory and strength exercises on disease activity for patients with inflammatory rheumatic diseases (IRDs). Design: A systematic review with meta-analysis registered at PROSPERO (CRD42015020004 ). Participants: Patients with IRDs. Data sources: The databases MEDLINE, AMED, Embase and CINAHL were searched from inception up to April 2016. Eligibility criteria for selecting studies: Trials were included if they were randomised controlled trials of adults with IRDs, comparing the effect of cardiorespiratory and strength exercises with usual care on disease activity and followed the American College of Sports Medicine's exercise recommendations. The primary outcome was disease activity in terms of inflammation, joint damage and symptoms. Data synthesis: Data were pooled in a random-effect model for all outcomes, and standardised mean differences (SMDs) were calculated. The quality of evidence was evaluated according to the Grading of Recommendations Assessment, Development and Evaluation approach. Results: Twenty-six trials with a total of 1286 participants were included. There was high to moderate quality evidence, for a small beneficial effect on disease activity scores (0.19 (95% CI 0.05 to 0.33), p<0.01) and joint damage (SMD 0.27 (95% CI 0.07 to 0.46), p<0.01). Furthermore, moderate quality evidence for a small beneficial effect on erythrocyte sedimentation rate (SMD 0.20 (95% CI 0.0 to 0.39), p=0.04) and for no effect on C reactive protein (SMD −0.14 (95% CI −0.37 to 0.08), p=0.21). Beneficial effects were also seen for symptoms. Conclusions: The results of this review suggest beneficial effects of exercises on inflammation, joint damage and symptoms in patients with IRDs.